Theoretical and Methodological Aspects of the Supply Chain Integration to Free Trade Zones - Z.K. Rajabova; O.R. Rajabov; M.M. Osmanov; T.A. Aigumov; M.G. Isaev; U.G.-G. Magomedova; B.A. Bachiev (International Journal of Supply Chain Management, 2020)
Abstract— The interdependence of resources in a global marketplace, the advancement of technology and rising national economic constraints have compelled companies to excel in their supply chain performance. To that end, Free Trade Zones (FTZs) may help supply chains improve their bottom line while generating economic development to their geographical regions. These zones have become a tool in most countries to stimulate the attraction of foreign investment, expand exports and / or create import-substituting industries, create new jobs, often in poles of economic growth, especially when forming complex zones in depressed regions through supply chain system. All these free economic zones allow states to realize mainly regional advantages in the efficiency of economic growth, the socio-economic development of the region, and have a multiplier effect on the development of the entire national economy of the free economic zone.